2008
DOI: 10.1074/jbc.m708620200
|View full text |Cite
|
Sign up to set email alerts
|

Allosteric Activation of the ATPase Activity of the Escherichia coli RhlB RNA Helicase

Abstract: Helicase B (RhlB) is one of the five DEAD box RNA-dependent ATPases found in Escherichia coli. Unique among these enzymes, RhlB requires an interaction with the partner protein RNase E for appreciable ATPase and RNA unwinding activities. To explore the basis for this activating effect, we have generated a di-cistronic vector that overexpresses a complex comprising RhlB and its recognition site within RNase E, corresponding to residues 696 -762. Complex formation has been characterized by isothermal titration c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(59 citation statements)
references
References 45 publications
1
42
0
Order By: Relevance
“…RraA forms a stable ternary complex with RNase E and helicase RhlB, in which all components can interact RhlB helicase binds strongly to the isolated 69-residue segment of RNase E that lies between the RBD and AR2 sites (K D of z10 nM) (Worrall et al 2008b). We tested whether RraA would bind to the stable binary complex of RhlB and RNase E(628-843), which encompasses the 69-residue helicase binding site and the flanking RNA-binding regions that were shown to be required for RraA binding in the previous section (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…RraA forms a stable ternary complex with RNase E and helicase RhlB, in which all components can interact RhlB helicase binds strongly to the isolated 69-residue segment of RNase E that lies between the RBD and AR2 sites (K D of z10 nM) (Worrall et al 2008b). We tested whether RraA would bind to the stable binary complex of RhlB and RNase E(628-843), which encompasses the 69-residue helicase binding site and the flanking RNA-binding regions that were shown to be required for RraA binding in the previous section (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…RNase E(628-843) construct is a fusion of RNase E sequence with a 13-residue leader and 20-residue C-terminal tail derived from its expression vector, pET11c. RNase E(696-762)/RhlB and RNase E(696-762)/RhlB(1-397) were purified as described previously (Worrall et al 2008b). During purification of these constructs, fractions from chelating chromatography lacking RNase E(696-762) were used as the source of RhlB or RhlB(1-397) alone.…”
Section: Overexpression and Purification Of Proteinsmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous work examining the Q motif of Rh1B helicase, Worrall et al conjectured that the communication between the ATPase catalytic center and the RNA-binding surface through the Q motif governs the mechanical power and efficiency of RNA helicases and is tuned to the cellular function of the helicase (15). Also, in the crystal structure of T4's gp17 (N360-ED), it was discovered that a structural difference occurred between the apo and ADP/ATP-bound states in the adenineinteracting loop (Cys-125-Arg-140) near Q143, suggesting that T4's Q motif (shown in Fig.…”
Section: The Q Motif Governs the Force-generating Ability Of A Viral mentioning
confidence: 99%
“…It was further proposed that the Q motif functions as a molecular on-off switch for ATP hydrolysis and helicase activity (14). Mutation studies in the Q motif in RNA helicases concluded that, at minimum, it directly regulates the affinity of the protein for the substrate (RNA) through conformational changes associated with nucleotide binding (14,15). Also, through sequence alignments of various terminases, Mitchell and Rao suggested that bacteriophage may have a deviant Walker A motif (76KSARVGYS83 unlike the classic Walker GXXXXGKS/T) responsible for interactions with the ␤ and ␥ phosphates of ATP (10,16,17).…”
mentioning
confidence: 99%